Churchill's "Iron Curtain" speech fifty years later - Muller, James W., 1953- (University of Missouri Press, 1999)
"Winston Churchill's visit to Fulton, Missouri, on March 5, 1946, marked the first public recognition of the cold war that was to follow World War II. Churchill delivered his most famous speech, "The Sinews of Peace," which became best known by the phrase he used to describe the cold-war division of Europe, the "iron curtain.""--Jacket